Association Between the COVID-19 Pandemic and Infant Neurodevelopment: A Comparison Before and During COVID-19 - Huang, Peiyuan; Zhou, Fengjuan; Guo, Yixin; Yuan, Shanshan; Lin, Shanshan; Lu, Jinhua; Tu, Si; Lu, Minshan; Shen, Songying; Guedeney, Antoine; Xia, Huimin; Qiu, Xiu (Frontiers in Pediatrics, 2021)
Aim: To investigate the association between the experience of the coronavirus disease 2019 (COVID-19) pandemic and neurodevelopment of six-month-old and one-year-old children and explore the differences in the association by birth order. Methods: This comparison study was embedded in the Born in Guangzhou Cohort Study in China. The exposed group included 546 six-month-old and 285 one-year-old children who attended neurodevelopment assessments between March 1 and May 15, 2020, and the non-exposed group included 3009 six-month-old and 2214 one-year-old children during the same months from 2015 to 2019. Neurodevelopment at age six months and one year was assessed by trained clinical staff using the Ages and Stages Questionnaires, third edition (ASQ-3) and the Gesell Developmental Schedules (GDS). Results: The experience of the pandemic in 2020 was associated with a higher risk of delay in the fine motor (adjusted OR: 2.50, 95% CI: 1.25, 4.99; estimated by logistic regression) and communication (adjusted RR [aRR]: 1.13, 95% CI: 1.02, 1.25; estimated by log-binomial regression) domains at age one year. The association between the experience of the pandemic and communication delay at age one year only existed in first-born children (aRR: 1.15, 95% CI: 1.03, 1.30) but not in later-born children (aRR: 1.02, 95% CI: 0.84, 1.25). No associations were observed in any domain among six-month-olds. Conclusions: Experiencing the COVID-19 pandemic and related public health strategies might be associated with a higher risk of delay in the development of fine motor and communication in one-year-old children; the association observed in the communication domain only existed in first-born children.